MAS-based distributed control method for multi-microgrids with high-penetration renewable energy. (15th March 2019) - Li, Qiang; Gao, Mengkai; Lin, Houfei; Chen, Ziyu; Chen, Minyou
Abstract: The distributed control of a multi-microgrid (MMG) system composed of neighboring microgrids (MGs) is much more complex than that of an MG. In this paper, a fully distributed control method with fault tolerance control for MMG systems is proposed, which is a two-layer model, where a communication network composed of agents is the top layer, while an MMG is the bottom layer. Further, a systematic method is presented to obtain a set of distributed control laws for agents from any given communication network. The communication network consists of two types of subgraphs, a within-MG subgraph and a between-MG subgraph. Moreover, the control laws derived from the within-MG subgraph ensure the supply-demand balance and the proportional outputs of distributed generators (DGs) in each MG, while the control laws derived from the between-MG subgraph coordinate MGs to achieve the power balance of the MMG system. Furthermore, two theorems and a proposition are proved, which state the convergence of the derived control laws. Finally, simulations are carried out on the MMG model in MATLAB/Simulink. The results show that the frequencies and voltages in MGs stay at the prescribed values, and the proportional outputs are achieved, when both loads and environmental conditions fluctuate. Furthermore, our distributed method has higher tolerance to the failures of agents, when compared to a centralized method. Highlights: A fully distributed two-layer control model is proposed for MMGs. A systematic method is presented to derive the distributed control laws for agents. Two theorems are proved, which ensure the convergence of the control laws. The proposed control method can tolerate failures of different types of agents.